Dmrt2 and Hmx2 direct intercalated cell diversity in the mammalian kidney through antagonistic and supporting regulatory processes - Riana K. Parvez; Doh Kyung Kim; Reka L. Csipan; Jinjin Guo; Zipeng Zeng; Chennan C. Zhang; Zhongwei Li; Andrew P. McMahon (Proceedings of the National Academy of Sciences, 2025)
Intercalated cells (ICs) in the mammalian kidney regulate circulatory pH through IC subtype–restricted actions of bicarbonate transporters: pH is elevated by Slc4a1 restricted to type A-ICs (A-ICs) and depressed by Slc26a4 in type B-IC (B-ICs). NonA-nonB-ICs (nA/nB-ICs) also produce Slc26a4 though their function is unclear. Though both nephron and ureteric progenitor lineages generate A-ICs, the former also generates nA/nB-ICs and the latter B-ICs. Lineage and cell type restricted transporter gene expression in the mouse and human kidney is preceded by expression of the transcriptional regulators Dmrt2/DMRT2 in A-ICs, and either, or both, Hmx2/HMX2 and Hmx3/HMX3 in B- and nA/nB ICs. CRISPR/Cas9-directed removal of Dmrt2 and the linked Hmx2 / Hmx3 genes resulted in IC-subtype switching. A-ICs adopted an Hmx2 + /Slc26a4 + B-IC cell fate on Dmrt2 removal while B-ICs initiated a Dmrt2 + /Slc4a1 + A-IC program on Hmx2/Hmx3 removal. Triple knockout of Dmrt2 , Hmx2 , and Hmx3 resulted in hybrid ICs expressing both Slc4a1 and Slc26a4 . Thus, restricted expression of these regulators is essential for specifying IC subtypes. To explore these mechanisms, Hmx2 and Dmrt2 were activated ectopically in ureteric organoid cultures. Introduction of Foxi1 —a pan determinant of ICs—activated early Dmrt2 + A-IC development while cointroduction of Hmx2 silenced Foxi1-dependent Dmrt2 expression and led to an upregulation of Slc26a4. In contrast, coexpression of Foxi1 and Dmrt2 upregulated Slc4a1 . These data support a model in which mutually repressive interactions between Dmrt2 and Hmx2/3 establish distinct IC identities and ongoing activity of these factors supports gene regulatory programs specific to each IC subtype.